‘Archaeology is but Ethnology in the past tense’. Theoretical Proofs and Intellectual Technologies in André Leroi-Gourhan’s Archived 'Archéologie du Pacifique-Nord', 1946 - Nathan Schlanger (Bulletin of the History of Archaeology, 2023)
The brief foray proposed here into the archives of French ethnologist, technologist and prehistorian André Leroi-Gourhan (1911–1986) focusses on the proof-correcting process of the very last page of his doctoral thesis, published in 1946. The changing state of these proofs and the additions he penned to them, as made perceptible in the illustrations provided, serves me to highlight three interconnected aspects of history-of-archaeology investigations: the interest of archives-based biographical studies, the links between the history and the theory of archaeology, and, last but not least, the material and ‘intellectual technologies’ involved in the production of knowledge. Résumé La brève excursion proposée ici dans les archives de l’ethnologue, technologue et préhistorien André Leroi-Gourhan (1911–1986) aborde spécifiquement la correction des épreuves de la toute dernière page de sa thèse de doctorat, publiée en 1946. Les différents états de ces jeux d’épreuves et les ajouts qu’il y a apportés, telles que perceptibles dans les images qui illustrent cet article, me servent à aborder trois aspects interconnectés de la recherche en histoire de l’archéologie: l’intérêt que présentent études biographiques à partir de fonds d’archives, les liens entre l’histoire et la théorie de l’archéologie, et enfin les dimensions matérielles des ‘technologies intellectuelles’ impliquées dans la production du savoir. Mots clefs: André Leroi-Gourhan; histoire de l’archéologie; théorie en archéologie; fond d’archives; histoire du livre; Protat Frères; ‘technologies intellectuelles’; culture matérielle; chaîne opératoire